Stand density and drought interaction on water relations of Nothofagus antarctica : contribution of forest management to climate change adaptability - Gyenge, Javier Enrique; Fernandez, María Elena; Sarasola, Mauro Miguel; Schlichter, Tomas Miguel (2017)
Nothofagus antarctica is the most representative species of the native mixed forest occupying ecotone areas between forests and steppe in NW Patagonia, South-America. In this type of environment, vulnerability to climate change is particularly enhanced. Predictions of future climatic conditions for this region indicate an increment of atmospheric temperature and also, a high variability of rain events, threatening forest persistence and productivity. In this framework, management strategies are crucial to guarantee sustainability of native vegetation systems. The objective of this study was to study the effect of tree density on the ecophysiological limitations of water use of N. antarctica, as a proxy to its productivity, during a drought period. Compared with the unthinned forest, the thinned forest showed higher soil water availability, higher sapflow density (Js) and canopy conductance (Gc) values, similar aerodynamic conductance (Ga) and a low degree of coupling to vapor pressure deficit. Ecophysiological results demonstrated a high limitation over gas exchange of individual N. antarctica trees imposed by the resistance in the hydraulic soil-to-leaf pathway in the unthinned-natural condition. Surprisingly, our results suggest structural limitations in the unthinned stand which reduce the ability of N. antarctica trees to take advantage of wet seasons, at least in the short term. Thinning could decrease the susceptibility of N. antarctica-based systems to drought stress, by increasing resource availability to the remaining trees, thus contributing to enhance the persistence of this species under climate change conditions.